2016
DOI: 10.1111/ggi.12687
|View full text |Cite
|
Sign up to set email alerts
|

Association between tooth loss and medical costs related to stroke in healthy older adults aged over 75 years in Japan

Abstract: Within the limitations of the present study, the reported findings suggest an independent relationship of tooth loss with increase in medical cost related to stroke among older Japanese adults. Further studies are necessary to substantiate these findings. Geriatr Gerontol Int 2017; 17: 202-210.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Socioeconomic factors, such as economic status and educational level, significantly affect health behaviors, including the use of medical institutions . In a study that examined the relationship between the number of teeth and the medical costs of stroke for those aged 80 years, income and education years did not show significant influences . Socioeconomic status is an important factor affecting various health conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Socioeconomic factors, such as economic status and educational level, significantly affect health behaviors, including the use of medical institutions . In a study that examined the relationship between the number of teeth and the medical costs of stroke for those aged 80 years, income and education years did not show significant influences . Socioeconomic status is an important factor affecting various health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The 2016 Survey of Dental Disease in Japan found that people aged ≥75 years had lost an average of approximately 10 teeth, and approximately 30% had full dentures . As a decline in chewing function after the loss of many teeth affects both dietary habits and nutrition intake, tooth loss is receiving increasing attention as an important factor affecting systemic health, including lifestyle‐related diseases, such as cancer, diabetes and cardiovascular disease; these conditions not only compromise health, but also increase medical costs . Therefore, tooth loss might increase not only dental care costs, but also overall medical costs because of the effects of dental health on systemic health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Associations between the number of teeth and systemic diseases 14 or mortality 15 are also reported. Furthermore, according to many studies, elderly people with 20 or more teeth can maintain good physical and mental health and high QOL 16 .…”
Section: Number Of Teethmentioning
confidence: 98%
“…In addition, conservation of remaining teeth has been reported to provide several advantages in the older population, including decreased incidence of dementia, arterial sclerosis and cardiovascular mortality . The association between tooth loss and increased medical costs has also been reported in adults over 75 years of age in Japan …”
Section: Introductionmentioning
confidence: 99%